Thực trạng công tác giáo dục hướng nghiệp ở các trường trung học phổ thông, trung tâm giáo dục nghề nghiệp - giáo dục thường xuyên trên địa bàn tỉnh Quảng Trị - Lê, Thị Xuân Liên; Nguyễn, Phong; Hồ, Đắc Vinh (Tạp chí Giáo dục, 2024)
Career orientation education in the 2018 General Education Program is a content with many new features. At the same time, many teachers implementing this program are accessing both the content and educational methods for the first time. Therefore, it is very necessary to learn about the reality of vocational education in high schools to support schools and teachers in effectively implementing this program. Survey results show that the school has difficulty advising students on career choices as well as helping students develop career-oriented study and training plans; teachers have limitations in understanding career guidance theory as well as skills in organizing career guidance activities; Many students have difficulty understanding themselves and determining careers that suit their abilities and strengths; Parents are interested in their children's career guidance, but most of them want their children to go to university, not colleges or vocational schools. On that basis, we research and propose contents to support schools, teachers, and students in implementing program content and vocational education methods to better comply with changing requirements. new education today.